Sale and leaseback property transaction in Malaysia / Nur Lesya Firsya Johami Ling - Johami Ling, Nur Lesya Firsya (2012)
This research is a study undertaken to investigate the perception of Investors and Corporation Companies in sale and leaseback transactions in Malaysia, in terms of which will be the objective of this research is to determine the factors that influence the corporate firm to be involved in sale and leaseback transactions and the effects of sale and leaseback. A research has been undertaken through interviews and questionnaire surveys among the Investors and Corporation Companies that are involved in sale and leaseback transactions. The findings of this study are: each of the Investors has different objectives and strategy in property investment industry while most of the Corporation Companies are from the manufacturing, sales and services background and they are not professional real property investor. Besides that, rental rates are typically fixed to provide for amortization of the purchase price over the term of the lease, plus a specified return rate on the Investor investment. In addition, sale and leaseback transaction usually involves a double or triple net lease arrangement and often includes an option for the Corporation Companies to renew their lease or repurchase the property.